Nutrient stock and water retention of liteira in three forest ecosystems in the eastern brazilian amazon (Research, Society and Development, 2021)
Water retention, stock and nutrients are parameters that allow characterizing a litter of an ecosystem. Following this thought or objective of the study, water retention, litter stock and nutrients in three successive different ecosystems were evaluated. The evaluated environments were an initial secondary forest, a late secondary forest and a secondary forest. Five 25 x 25m plots were marked, where seven parts / plots were randomly collected in two periods. totaling 35 dimensions per ecosystem per period. As the samples were subjected to a statistical analysis for water retention capacity data and a stock of photographs, and nutrient analysis. The results of water retention show that, in the less rainy period, the initial and primary secondary forests were different and larger than the late secondary. In the litter stock, there were differences in the two periods with the largest amount for agricultural forest. Regarding nutrient analysis, the highest nitrogen value was for primary forest; Phosphorus was a late secondary forest, and there was no significant difference between ecosystems. This concludes the three ecosystems that differ in water retention; without litter stock and nutrient values, evidence that successive level directly influences these variables.